2002
DOI: 10.1063/1.1518147
|View full text |Cite
|
Sign up to set email alerts
|

Optical study of redox process of Ag nanoparticles at high temperature

Abstract: An optical study of the redox of Ag nanoparticles was carried out by loading the particles into the pores of monolithic mesoporous silica. The optical absorption of silver nanoparticles was measured after annealing in different atmospheres. It has been found that treatment in H2 or N2 induces a strong surface plasmon resonance (SPR) as usually expected, but air-annealing results in disappearance of such SPR. Alternate annealing in air and H2 (or N2) induces alternant disappearance and appearance of the SPR abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
61
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 20 publications
7
61
0
Order By: Relevance
“…(a) Air exposed sample NP1 (b) Air exposed sample PC FULL PAPER modynamic calculations on silver nanoparticles has shown that the formation of oxide shell is energetically favorable only up to a critical shell thickness. [36] Thus, the changes in the optical and electrical properties of Gd nanoparticles on exposure to air can be explained by the formation of a Gd x O y shell around the Gd nanoparticles during the initial exposure time. It is also possible that the as-deposited Gd nanoparticles have a small Gd x O y surface layer, which grows on exposure to air only up to a certain thickness.…”
Section: Resultsmentioning
confidence: 99%
“…(a) Air exposed sample NP1 (b) Air exposed sample PC FULL PAPER modynamic calculations on silver nanoparticles has shown that the formation of oxide shell is energetically favorable only up to a critical shell thickness. [36] Thus, the changes in the optical and electrical properties of Gd nanoparticles on exposure to air can be explained by the formation of a Gd x O y shell around the Gd nanoparticles during the initial exposure time. It is also possible that the as-deposited Gd nanoparticles have a small Gd x O y surface layer, which grows on exposure to air only up to a certain thickness.…”
Section: Resultsmentioning
confidence: 99%
“…Synthesis, size control and catalysis of noble metal nanomaterials have been intensively investigated [5]. However, their chemical reactivity has been little explored [6][7][8]. Silver (Ag) is a noble metal with an inert chemical reactivity in its bulk form and is listed below hydrogen in the activity series of metals.…”
Section: Introductionmentioning
confidence: 99%
“…Complete oxidation does not occur due to the passivation of the surface by the oxide shell, as in other metal nanoparticle systems. 27 Based on the oxygen XPS data, the In 3+ species is predominantly an indium hydroxide, which has previously been implicated as the catalytic resting state for CO 2 reduction on indium and the site at which CO 2 can chemisorb and be reduced as the carbonate. 7 The metallic core provides a conductive path for electrons to flow from the carbon black support to the catalytic surface, unlike in the pure In 2 O 3 and In(OH) 3 particles, which are more insulating and allow the carbon black to evolve hydrogen.…”
mentioning
confidence: 99%